An Assessment of Different Factors on the Location the Subsurface dams in the Province of Kohgiloyeh and Boyerahmad - Majid Khazaei; Mirmsoud Kheirkhah Zarkesh; Mohammad Reza Mirzaei; Iman Saleh; Farahnaz Azizi (پژوهش‌های آبخیزداری, 2021)
Water shortage in the arid and semi-arid regions has necessitated subsurface dam construction for groundwater storage. The aim of this study was to determine the appropriate locations for subsurface dam construction using a set of field, laboratory and software methods in the arid and semi-arid regions of the provinces of Kohgiluyeh and Boyerahmad. Six axes were selected by examining the topographic maps and the drainage network. The most important factors influencing the subsurface dam construction were selected. Using the average expert opinion benefitting from a questionnaire and employing the FUZZY-AHP method, suitable places for subsurface dam construction were prioritized. Considering the geophysical studies, the characteristics of the affected strata were determined. The results of prioritization of suitable locations for subsurface dam construction showed that the Tang Nayab with a weight of 0.41 holds the top ranking. The study of the results of the most important factors affecting in subsurface dams construction indicated that water supply and bed-rock with a combined weight of 0.25 is the most effective factor in subsurface dam construction. The results of geophysical surveys also indicated that the alluvium strata had an electrical resistance of 300 to 400 ohm-meter. The results of geophysical surveys indicated that the alluvium thickness in selected site is 5 m.